Effect of collection time and dormancy breaking treatments on seed germination of Prangos ferulacea L. - T. Bazi; َAli Moradi (علوم و فناوری بذر ایران)
Prangos ferulacea L. is a plant from Apiaceae family which is used in medicinal and forage industries.  Because of problems during germination and growth of this plant, several experiments were conducted in order to break dormancy and its germination enhancing. Seed samples were collected from their natural habitats (ridge of Vezg, Kogiluyeh and Boyerahmad province) in three dates of 7, 17 and 27 June 2012 and possibility of dormancy breaking were examined in the form of three separate experiments with three replicates. The first experiment factors consisted of three levels of collecting time (mentioned above) and GA3 in two levels (1000 and 1500 mg.l-1) which were applied along with 2 week’s moist chilling. The second experiment was consisted of collecting time at three levels along with moist chilling, that chilling was applied for four weeks. The third experiment factors were consisted of seed collection time in three levels and germination temperatures at two levels (15 and 20 ̊C). The Seeds were moist-chilled at 4°C for 8 weeks and then transferred to the incubators with the temperatures of 15°C and 20 °C. In the first experiment, germination of seeds collected in the third date and treated with GA 1500 mg.l-1 (33.6%) was higher than that of 1000 mg.l-1 (17.6%). The second study showed a significant positive effect of collecting time on seed germination of this plant, so that germination of seeds collected in the third date was almost doubled compared to the first date. The thirds experiment results showed that the temperature of 15 °C is more suitable than 20 °C for Prangos ferulacea seed germination. In all the three experiments the highest germination (33.26% in the first, 33.61 % in the second and 43.02% in the third experiments) were achieved when the seeds were collected at full maturity. Seeds germination obtained from 8 weeks (30.52%) chilling was higher than that of two (13.15%) and four weeks (27%). The overall results showed that Prangos ferulacea seeds have levels of physiological dormancy and seed maturity level at the time of collecting have significant effect on seed germination of this plant.